Development of Physics Digital Comic on Greenhouse Effect - Rachmawati, Siti; Muliyati, Dewi; Purwahida, Rahmah (Current STEAM and Education Research, 2023)
Around 20% of the total population in Indonesia are digital comic readers and this number continues to increase from year to year. This increase has been accompanied by a rise in the number of digital comics on various platforms such as Webtoon, Mangatoon, Bilibili Comics, Manta,Tapas, RE:ON comics, Komikindo v7 and many more. On the other hand, the complexity of the teaching materials being delivered made students less interested in reading textbooks, including physics. Therefore, students are more engaged when the content is presented in the form of illustrated comics, especially in visualizing abstract concepts. This study aims to produce digital physics comics about the greenhouse effect, which can enchance students' literacy and motivation. It’s well known that global warmingis a global issue that demands a broader understanding and is important to be recognized by the public including students, where one of the causes is the greenhouse effect. This comic seeks to support physics learning media. This study uses Research and Development (R&D) approach with a 4D method. The development stages consist of defining, designing, developing and disseminating. This physics digital comic explains the process of the greenhouse effect. This research shows that digital comics that have been developed have successfully become physics learning media that can increase students' literacy and motivation to learn about global warming and climate change.